Towards a Bad Bitches' Pedagogy. (14th October 2022) - Ali, Khalilah
Abstract : In this paper, I present a personal narrative approach, grounded in Connelly and Clandinin's ontological and epistemological stance that "humans are story-telling organisms"1 to discuss my construction of a uniquely working class Black feminist educator identity. This narrative inquiry is an adapted counter-methodological researcher approach that was born out of an interlinkage of my explorations into the histories of Black women educators, hip hop feminisms, and Higginbotham's respectability politics, 2 as it is understood in popular cultural terrain, and as the concept contrasts with and complements notions of (dis)respectability. I situate the paper within a critical hip hop feminist framework and access raunch aesthetics' use of the sartorial and performative bad-assedness to understand how I have come to craft a transgressive teacher identity. By embracing a vernacular transgressive archetype of the bad bitch pedagogue, I analyze and complicate my own intersectional identity as a working-class Black woman who navigated an adversarial bourgeoisie traditionalist educational system as a teacher, unwed custodial parent, cultural worker and advocate for Black youth.